PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) DALAM PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Mursidah, Faizatul; Hendratno; Pristanti, Mahallisa Dyah; Yatimah, Nanik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve students' critical thinking skills through an approach Teaching at the Right Level (TaRL) in learning Problem Based Learning (PBL). The research method used was classroom action research (PTK) involving class III D students at SDN Kedurus III/430 Surabaya. This research was carried out in two cycles starting with action planning, learning implementation, observation and reflection. Data collection was carried out using test sheets to measure students' critical thinking abilities. The research results show that the application of the TaRL approach in the PBL model can significantly increase students' critical thinking abilities which can be seen from the results of the percentage of students in cycle 1, namely 50.34% with the critical thinking indicator providing a simple explanation. The percentage results on student indicators provide further explanation, namely 67.24%. The critical thinking indicator for building basic skills produces a percentage of 68.96%. The percentage result of the indicator analyzing data is 68.96% and the percentage result of the indicator identifying assumptions and deciding on alternatives for solutions is 58.62%. In cycle 2 activities there was an increase in the percentage of students' critical thinking skills, namely in the indicator of providing simple explanations with a percentage of 86.20%, in the indicator of making further explanations there was a percentage of 83%, building skills produced a percentage of 86.20%, indicators of analyzing data produced a percentage 86.20%, and the indicator of identifying assumptions and deciding on alternatives for solutions produces a percentage of 87.93%.